Pengaruh Total Resistance Terhadap Produksi Dump Truck Lgmg CMT96 Pada Pengangkutan Overburden PT Ansaf Inti Resources Kabupaten Kutai Kertanegara Provinsi Kalimantan Timur - Arsuwendi Arsuwendi; Harjuni Hasan; Albertus Juvensius Pontus (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
PT Ansaf Inti Resources is a company engaged in coal mining using the open pit method. In the process of mining in open pit mines, haul roads are indispensable in the process of transporting overburden and play an important role in the mining production cycle. The purpose of the study is to determine the total resistance to overburden production of the LGMG CMT96 conveyance based on the haul road segment that has been determined from the overburden loading point to the disposal of the material, then a calculation is made based on the standard number of good total resistance to the actual haul road. After calculating all segments of the haul road, the results of plotting the total obstacle graph against the speed, travel time, and production of the haul. So every 1% increase in total resistance will reduce the speed of the conveyance 1.346 km / h, while every 1% increase in total resistance will reduce the travel time of the conveyance 0.0464 minutes. The production results of the CMT96 conveyance before the improvement of the total obstacle to the road surface amounted to 55 lcm and 49 lcm, while after the improvement of the total obstacle to the road surface there was an increase in the production of the conveyance of 68 lcm and 62 lcm. So every 1% increase in total resistance will reduce the production of conveyance by 4.7429 lcm.